NON-VOLANT MAMMALS OF THE SERRA DA MACACA PARK ROAD (SP-139), SOUTHEASTERN BRAZIL - Alves, Francisco de Assis [UNESP] (2022)
The objective of this study was to survey non-volant mammals at Serra da Macaca Park Road (SP-139), particularly during road daily closure. Visual searches and camera traps were used to record mammals, and estimator Jackknife to estimate the expected richness. Differences in diversity were calculated using the Shannon-Wiener index (H’). In total, 12 species of non-volant mammals, four of them considered threatened, were sampled. Additionally, roadkills of the non-volant mammals were recorded too. The absence of some predominantly nocturnal species from the list of the roadkilled non-volant mammals was noticeable. The results highlight the importance of the temporary road closures, during periods of high mammal activity.